Chemical composition of goniothalamus andersonii bark and its mosquito repellent activity - Saripah Salbiah Syed Abdul Azziz (Tanjung Malim, 2023)
Chemical composition of goniothalamus andersonii bark and its mosquito repellent activity by Saripah Salbiah Syed Abdul Azziz